Clinical Insights and Future Prospects: A Comprehensive Narrative Review on Immunomodulation Induced by Electrochemotherapy - Martina Ferioli; Anna Myriam Perrone; Pierandrea De Iaco; Arina A. Zamfir; Gloria Ravegnini; Milly Buwenge; Bruno Fionda; Erika Galietta; Costanza M. Donati; Luca Tagliaferri; Alessio G. Morganti (Current Oncology)
Electrochemotherapy (ECT) is an emerging therapeutic approach gaining growing interest for its potential immunomodulatory effects in cancer treatment. This narrative review systematically examines the current state of knowledge regarding the interplay between ECT and the immune system. Through an analysis of preclinical and clinical studies, the review highlights ECT capacity to induce immunogenic cell death, activate dendritic cells, release tumor antigens, trigger inflammatory responses, and occasionally manifest systemic effects—the abscopal phenomenon. These mechanisms collectively suggest the ECT potential to influence both local tumor control and immune responses. While implications for clinical practice appear promising, warranting the consideration of ECT as a complementary treatment to immunotherapy, the evidence remains preliminary. Consequently, further research is needed to elucidate the underlying mechanisms, optimize treatment protocols, explore potential synergies, and decipher the parameters influencing the abscopal effect. As the field advances, the integration of ECT’s potential immunomodulatory aspects into clinical practice will need careful evaluation and collaboration among clinical practitioners, researchers, and policymakers.